The Role of Identity and Gender Beliefs in Self-Identification of Abuse for Male Victims of IPV - Vail, Summer L. (Journal of interpersonal violence, 2025)
Men experience numerous barriers in seeking help or resources after intimate partner violence (IPV) victimization, with one barrier being a reluctance or lack of ability to identify that they have been victims of IPV. This study examines factors relating to male victims of IPV self-identification of abuse. Using a gender socialization approach, demographics and facets of masculine honor ideology were tested to see whether they were significantly related to self-identifying as experiencing abuse in their relationship. Using a sample of 289 men, the frequency of individuals who self-identified as someone who had been in an abusive relationship was compared to the number of individuals who indicated IPV victimization on the Revised Conflict Tactics Scale (CTS2), and percentages of correct identification were calculated. In addition, a binary logistic regression was run to examine factors that were related to someone identifying as a victim of IPV compared to those that were not. When directly asked if they had ever experienced abuse in a romantic relationship, a total of 41 (14.2%) men self-identified as having been a victim of IPV. However, when examining scores on the CTS2, 69 (23.9%) reported some sexual IPV, 201 (69.6%) indicated psychological abuse, and 59 (20.4%) indicated physical abuse. Subscales of the Masculine Honor Belief Scale were not found to have a significant relationship with self-identification, but differences were found among types of IPV and demographics. Specifically, men who identify as LGBTQ+ were significantly more likely to identify when they experienced IPV victimization. Barriers to male self-identification and treatment are discussed.